Importance of Timing of Platelet Lysate-Supplementation in Expanding or Redifferentiating Human Chondrocytes for Chondrogenesis - Rikkers, Margot; Levato, Riccardo; Malda, Jos; Vonk, Luciënne A. (Frontiers in Bioengineering and Biotechnology, 2020)
Osteoarthritis (OA) in articular joints is a prevalent disease. With increasing life expectancy, the need for therapies other than knee replacement arises. The intrinsic repair capacity of cartilage is limited, therefore alternative strategies for cartilage regeneration are being explored. The purpose of this study is first to investigate the potential of platelet lysate (PL) as a xeno-free alternative in expansion of human OA chondrocytes for cell therapy, and second to assess the effects of PL on redifferentiation of expanded chondrocytes in 3D pellet cultures. Chondrocytes were isolated from human OA cartilage and subjected to PL in monolayer culture. Cell proliferation, morphology, and expression of chondrogenic genes were assessed. Next, PL-expanded chondrocytes were cultured in 3D cell pellets and cartilage matrix production was assessed after 28 days. In addition, the supplementation of PL to redifferentiation medium for the culture of expanded chondrocytes in 3D pellets was evaluated. Glycosaminoglycan (GAG) and collagen production were evaluated by quantitative biochemical analyses, as well as by (immuno)histochemistry. A dose-dependent effect of PL on chondrocyte proliferation was found, but expression of chondrogenic markers was decreased when compared to FBS-expanded cells. After 28 days of subsequent 3D pellet culture, GAG production was significantly higher in pellets consisting of chondrocytes expanded with PL compared to controls. However, when used to supplement redifferentiation medium for chondrocyte pellets, PL significantly decreased the production of GAGs and collagen. In conclusion, chondrocyte proliferation is stimulated by PL and cartilage production in subsequent 3D culture is maintained. Furthermore, the presences of PL during redifferentiation of 3D chondrocyte strongly inhibits GAG and collagen content. The data presented in the current study indicate that while the use of PL for expansion in cartilage cell therapies is possibly beneficial, intra-articular injection of the product in the treatment of OA might be questioned.